Divided politics and economic growth in the Philippines - Batalla, Eric Vincent C. (Animo Repository, 2016)
© 2016, GIGA German Institute of Global and Area Studies. All rights reserved. As the 2016 elections drew near and the prospects of a Rodrigo Duterte presidency became stronger, there were concerns that the economy might be adversely affected by the expected political volatility under the new regime. Since the start of the campaign season, Duterte had been rocking the establishment through controversial pronouncements and outbursts, attracting the enmity of leaders of the Catholic Church, the United States, and the United Nations. Based on a review of recent political and economic performance, this article argues that unless there are significant changes in the major sources of macroeconomic growth and stability, the Philippine economy would likely withstand the impact of a “Duterte shock.”